An investigation into linguistic features of annotations in english and vietnamese - Nguyễn,Thị Ngọc Ánh (ĐHĐN., 2015)
This paper is to study the structural, syntactic and semantic features of English and Vietnamese annotations. The thesis involves both qualitative and quantitative data analysis through 150 annotations in English and 150 annotations in Vietnamese which are collected from the language website http://www.natcorp.ox.ac.uk/ and textbooks, stories and novels by well-known writers in both languages.The findings show that annotations in English and Vietnamese have remarkable structural, syntactic and semantic features and there are some similarities and differences between English and Vietnamese. In addition, the study also suggests some implications for language teaching activities and for learners to master English linguistic features.